Reactive oxygen species–resistant ultrastable super-resolution DNA framework dots - Chengpin Liang; Qingting Li; Bin Chen; Tingting Zhai; Xiaoqian Luo; Yang Yang; Jiang Qian; Dan Zhao; Shihua Luo; Fei Wang; Qian Li; Jianlei Shen; et al. (Proceedings of the National Academy of Sciences, 2026)
Nanoconfinement as observed in natural (e.g. green fluorescent protein, GFP) or artificial (metal-organic or covalent organic frameworks) systems effectively modulates chemical and physical properties of encapsulated molecules for various photonic, electronic, or catalytic applications. Inspired by GFP’s barrel-like peptide scaffold, which stabilizes the chromophore within a confined space, here we develop photobleaching-resistant super-resolution DNA framework (SDF) dots that enables programmable confinement of various types of fluorophores within the inner cavity resembling GFP. We find that SDF dots are resistant to reactive oxygen species-induced photobleaching due to the shielding effects of DNA frameworks. SDF dots with four fluorophores labeling inside of the cavity leads to ~1.8-fold enhancement in photostability compared to the corner labeling, whereas ~50-fold enhancement compared to single fluorophore labeled on double-stranded DNA. These ultrastable SDF dots are readily adaptable for super-resolution imaging including stimulated emission depletion (STED) and structured illumination microscopy (SIM) imaging. We realize STED imaging of live cell membranes over 30 min. We further construct ultrastable super-resolution SIM barcodes that can distinguish eighteen colored barcodes with a spatial resolution of ~70 nm. This strategy provides a versatile platform for engineering ultrastable fluorescent probes for advancing super-resolution imaging and single-particle tracking in biophysics and biomedical research.